2017
DOI: 10.1101/183186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic sequencing identifies secondary findings in a cohort of parent study participants

Abstract: PURPOSE: Clinically relevant secondary variants were identified in parents enrolled with a child with developmental delay and intellectual disability. METHODS: Exome/genome sequencing and analysis of 789 'unaffected' parents was performed. RESULTS: Pathogenic/likely pathogenic variants were identified in 21 genes within 25 individuals (3.2%), with 11 (1.4%) participants harboring variation in a gene defined as clinically actionable by the ACMG. Of the 25 individuals, five carried a variant consistent with a pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…90% of the reviewed articles reported incidental finding frequencies between 0.5% and 6.5% in their studied cohorts and two studies reported a frequency of incidental findings above 12% (9,19). The higher frequency could be partially explained by the use of different gene lists to return the incidental findings; as some studies preferred to include a more comprehensive list of genes with actionable variants (9,13,21,22,41,61).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…90% of the reviewed articles reported incidental finding frequencies between 0.5% and 6.5% in their studied cohorts and two studies reported a frequency of incidental findings above 12% (9,19). The higher frequency could be partially explained by the use of different gene lists to return the incidental findings; as some studies preferred to include a more comprehensive list of genes with actionable variants (9,13,21,22,41,61).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen reviewed articles restricted the analysis of the incidental findings to the 56/59 ACMG genes. The difference between the total reported frequency of participants with incidental findings and the frequency of participants with incidental findings in the 56/59 ACMG genes ranged between 0.3% to 2.34% in five studies (13,19,21,22,41), while Rego et al reported an 8.5% difference (9).…”
Section: Frequency Of Incidental Findingsmentioning
confidence: 91%
See 3 more Smart Citations